Spotlight on the treatment armamentarium of concomitant psoriasis and inflammatory bowel disease: a systematic review. (3rd April 2022) - Conforti, Claudio; Dianzani, Caterina; Zalaudek, Iris; Cicala, Michele; Persichetti, Paolo; Giuffrida, Roberta; Morariu, Silviu-Horia; Neagu, Nicoleta
Abstract: Background: Psoriasis and inflammatory bowel diseases share common immunological pathomechanisms and therefore similar treatment options. Objective: To assess already existing therapies and their efficacy versus adverse effects and paradoxical reactions in patients presenting with either disease or both. Data sources: A systematic search of the PubMed and Science.gov databases was performed for the period 2018–2020. Only articles in English were selected. Search terms included a combination of keywords: adalimumab, infliximab, etanercept, golimumab, certolizumab, ustekinumab, guselkumab, vedolizumab, secukinumab, ixekizumab, brodalumab, acitretin, cyclosporine, methotrexate, apremilast, mycophenolate mofetil, sulfasalazine, hydroxyurea, azathioprine, 6-thioguanine, tacrolimus, leflunomide and fumaric acid esters in combination with each of the following: paradoxical, psoriasis, psoriatic arthritis, inflammatory bowel disease, Crohn's disease, ulcerative colitis. Other potentially relevant articles were identified by manually checking the references of the included literature. Study selection: Recent reviews and meta-analyses, pooled analyses, cohort studies, observational studies, care reports were all included. Conclusions: Psoriasis and IBD can be treated concurrently as they share common inflammatory pathways. TNF-α inhibitors and IL-12/23 have been successful in treating both psoriasis and IBD. IL-17 inhibitors are recognized treatments for psoriasis but have the potential to exacerbate IBD. Newer molecules require further clinical trials and real-life studies in order to confirm their efficacy and safety.